Effectiveness of Education Program on Nurses' Knowledge aboutthe Use of Physical Restraints for Patients in Intensive Care Unit - Dheef, Saad Ahmed; Mohammed, Widad K. (Iraqi National Journal of Nursing Specialties, 2023)
Objective(s): Evaluation of effectiveness of the education program on nurses' knowledge about the use of physical restraints for patients at intensive care unit.Methods: A quasi-experimental study was conducted on a purposive (non-probability) sample of 40 male and female nurses working at intensive care unit in Al-Nasiriyah teaching hospital from the seventh day of January 2023 to the eighth day of February 2023. An education program was prepared and presented to the nurses and a questionnaire of knowledge was constructed and used to evaluate their knowledge at the pre-and post-test of implementation of the program. The study instrument and education program were presented to 11 experts for the purpose of verifying from validity, as for the reliability of the instrument, it was done through the use of a test-retest method, where the result was = 89. Data was analyzed using SPSS VERSION 23.Results: The study results showed there are statistically significant differences between the pre-and post-test for the study group at P < 0.05.Conclusion: The study concluded that the education program on nurses’ knowledge was effective on study group through improving their knowledge.Recommendation: The study recommend that the current education program should be provided to all nurses in the intensive care unit because of its utmost importance in improving the knowledge of nurses.